Management of tobacco smoking in the prison service units - The effects of the health promotion program - Krzysztof Puchalski; Elżbieta Korzeniowska (Nofer Institute of Occupational Medicine, 2016)
Background: In 2014 the health promotion program aimed at managing personnel smoking was implemented in the Polish prison service (PS) in cooperation with the Nofer Institute of Occupational Medicine (NIOM). It combined education of managers, encouraging them to implement good practices, with employees' education. This paper describes the process of implementation and its effects in 159 units of PS, against the data on the management of smoking in medium and large companies in Poland gathered in 2010. Material and Methods: Situations concerning smoking management in PS units before and after a half-year program implementation were compared. Data were gathered using self-diagnosis questionnaires (initial and final assessments) collectively filled in by representatives of management and employees. Results: Due to the program implementation there was an increase in the percentage of PS units with known number of smoking employees (19% vs. 61%), consultions on formal smoking regulations with personnel (14% vs. 57%), minimal antismoking medical interventions (46% vs. 59%), and assessments of effects of antismoking activities (14% vs. 55%). There was also increase in the number of PS units with personnel totally obeying smoking regulations (28% vs. 41%) and decrease in those where such rules are not completely met (9% vs. 7%). In 3/4 PS units there was an increase in employees' interest in quitting smoking and in 40% of them employees smoke less at work. Almost every second unit has set up a health promotion team. Conclusions: In many aspects the program has brought along satisfying effects and allowed for depicting areas of improvement. Its scheme and tools can be used, after adaptation, in interventions concerning other health problems in workplaces. Med Pr 2016;67(5):605-621